2021
DOI: 10.1016/j.jseint.2021.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Increasing severity of anemia is associated with poorer 30-day outcomes for total shoulder arthroplasty

Abstract: Background Total shoulder arthroplasty (TSA) has increased in utilization over the past several decades. Anemia is a common preoperative condition among patients undergoing TSA and has been associated with poorer outcomes in other surgical procedures. To the best of our knowledge, no study has analyzed the association between anemia severity and TSA outcomes. Therefore, the purpose of this study is to determine the effects that increasing severity of anemia may have on the postoperative outcomes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Our study revealed a signi cant association between preoperative anemia (HCT < 39% in males and < 36% in females) and postoperative DVT in patients with lower limb bone trauma, which aligns with the results of previous studies [7], to avoid the interference of blood transfusion on the research results, we performed separate analyses for patients with and without blood transfusion respectively. Our results showed that in patients without perioperative blood transfusion, mild anemia only slightly increased the incidence of postoperative DVT (OR:1.369, 95%CI [0.839-2.236], p = 0.209), which was consistent with previous ndings [5,8]. However, the postoperative DVT risk in patients with moderate to severe anemia in the three groups was 1.742, 2.056, and 3.373 times higher than that in patients without anemia, respectively.…”
Section: Relationship Between Preoperative Anemia Of Different Degree...supporting
confidence: 93%
See 1 more Smart Citation
“…Our study revealed a signi cant association between preoperative anemia (HCT < 39% in males and < 36% in females) and postoperative DVT in patients with lower limb bone trauma, which aligns with the results of previous studies [7], to avoid the interference of blood transfusion on the research results, we performed separate analyses for patients with and without blood transfusion respectively. Our results showed that in patients without perioperative blood transfusion, mild anemia only slightly increased the incidence of postoperative DVT (OR:1.369, 95%CI [0.839-2.236], p = 0.209), which was consistent with previous ndings [5,8]. However, the postoperative DVT risk in patients with moderate to severe anemia in the three groups was 1.742, 2.056, and 3.373 times higher than that in patients without anemia, respectively.…”
Section: Relationship Between Preoperative Anemia Of Different Degree...supporting
confidence: 93%
“…Preoperative anemia is highly prevalent in patients with bone trauma, which the rate could be raised to 24-47.9% [4][5][6], and there are limited number of studies have found that anemia is a possible risk factor for perioperative DVT in patients with bone trauma currently [4,7,8]. Preoperative anemia associated with increased worse postoperative outcomes and length of stay, moreover, a decrease in the mass of red blood cells during anemia may leads to tissue hypoxia and iron de ciency associated with an increased concentration of factor VIII, all are risk factors for thrombosis [5,9]. Red blood cells play an essential role in formation of thrombosis, and the mechanism by which high hematocrit (HCT) levels promote venous thrombosis through increased blood viscosity has been recognized.…”
Section: Introductionmentioning
confidence: 99%
“…9 We found that increased severity of anemia resulted in greater length of hospital stay from 2.3 days in nonanemic patients to 4.9 days in severely anemic patients. Doan and colleagues 11 demonstrated similar stepwise increased LOSs following total shoulder arthroplasty from 1.6 days to 3.0 days as severity of anemia worsened. As orthopedic surgery transitions into value-based care through bundled payment models, cost-controlling measures such as limiting short-term complications, readmissions, and reoperations remain paramount.…”
Section: Discussionmentioning
confidence: 89%
“…9 In total joint arthroplasty of the shoulder, preoperative anemia severity has been demonstrated to influence perioperative complications including blood transfusions and other major complications. [10][11][12] Furthermore, intraoperative blood transfusion has been shown to be associated with a higher risk of mortality and morbidity in surgical patients with severe anemia. 13,14 No studies to date have evaluated the impact of anemia severity on outcomes after primary TEA.…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing evidence has shown that red blood cells play an active role in blood coagulation [7][8][9], beyond changes in blood ow mechanics. The preoperative anemia rate in patients with bone trauma range from 24-47.9% [5,10,11],…”
Section: Introductionmentioning
confidence: 99%